OPTIMIZING GREEN FISCAL POLICY FOR CIRCULAR ECONOMY DEVELOPMENT IN INDONESIA : An Islamic Economic Perspective - Yunanda, Fayeno; Abdullah, Muslem (Program Studi Hukum Ekonomi Syariah Fakultas Syariah dan Hukum UIN Ar-Raniry, 2026)
The transition toward a circular economy has become a key strategy for addressing environmental degradation, resource scarcity, and sustainable industrial development. In Indonesia, however, fiscal support for the circular economy remains fragmented and has not yet been established as a distinct budget line, limiting its role in accelerating industrial transformation.From the perspective of Maqāṣid al-Sharī'ah, green fiscal policy is expected to promote public welfare (maṣlaḥah) through sustainable resource management. This study examines APBN allocation in supporting the circular economy, identifies effective green fiscal policy instruments based on international evidence, and develops an APBN optimization framework aligned with the objectives of Maqāṣid al-Sharī'ah. The study employs a qualitative approach using a systematic literature review, comparative policy analysis, and qualitative content analysis. The findings indicate that performance-based environmental tax incentives, targeted green subsidies, and increased public investment in research, innovation, and recycling infrastructure are the key fiscal instruments for accelerating the transition toward a circular economy. Integrating these instruments into the APBN can strengthen industrial competitiveness, improve environmental sustainability, and support the realization of Maqāṣid al-Sharī'ah through sustainable economic development.